O sistema multiportas como política pública de acesso à justiça e de efetividade dos direitos fundamentais - Nascimento, Meire Rocha do (2021)
In contemporary society, there is a growing number of legal problems and conflicts of interest that generate disputes that flow into the Judiciary. Although Brazil guarantees access to justice or the inescapability of jurisdiction, a fundamental human right, under the terms of art. 5, item XXXV of the Citizen Constitution of 1988, this does not mean that every conflict must be resolved, necessarily, through the traditional jurisdictional means, culminating in the solution of the dispute, via the judge's sentence. The field of appropriate dispute resolution (ADR) comprises methods suitable for conflict resolution, which provide options for reaching a consensus, considering the factual context of the dispute. The Multi-Door Courthouse is a new form of judiciary organization, which sees the Judiciary as a dispute resolution center, which can provide citizens with the choice of different processes for each case, bearing in mind the principle that the advantages and disadvantages of each procedure must be considered, according to the peculiarities of each conflict. Thus, the research had as general objective to investigate the introduction of the Multi-Door System in the Brazilian legal system and its adoption as a public policy for access to justice and the effectiveness of fundamental rights, the criteria of admissibility and application, the reach of benefits such as social pacification, the celerity and effectiveness of the jurisdictional provision. The study was carried out based on qualitative research, adopting the hypothetical-deductive method, with a bibliographic survey, legislative and documental analysis. The methodology used in policy evaluation involved the analysis of statistical models, with a focus on the implementation cycle. The research explored the Multi-Door System, which deals with new models that enable the parties, via a participatory procedure, to constructively resolve their disputes by reinvigorating social relations, knowing latent conflict interests, stimulating cooperation, using means of preventing future controversies, and encourage those involved to have a better understanding of each other. This thesis was organized into three chapters, the first of which presented access to justice and the Multi-Door System, from a broader and more substantive view; the second dealt with the current state of the art of the Multi-Door System in Brazil; the third encompassed the evaluation of the Multi-Door System as a public policy and pointed out the challenges for the future. It was found that the Multi-Door System, although originating from foreign law, meets the needs of the Brazilian population, it does not constitute "second class" justice for the masses of the country, being used, regardless of social class, without distinguishing or prejudice, due to the inherent advantages, such as celerity, empowerment of the parties, conflict resolution and social pacification, it constitutes a public policy for the adequate treatment of conflicts of interest, it contributes to reducing the congestion rate of the Brazilian Judiciary, and guarantees the effectiveness of fundamental rights, with the expansion and substantiation of the concept of access to justice, as a means of guaranteeing citizens the good of life.